Gambaran Karakteristik dan Status Gizi Anak yang Melakukan Vaksinasi Covid-19 di UPT Puskesmas Kayon Kota Palangka Raya - Rafli, Muhammad Rafli Adryannoor; Sri Yuliani, Ni Nyoman; Faradila (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
Achievement of the COVID 19 vaccination target, especially for children who received dose 2, has only reached 58.7%. One of the obstacles to achieving the vaccination target is the delay in vaccination because the child is sick. Health conditions at the time of vaccination are sought to be healthy and optimal. Nutritional status has an important role in determining the body's immune response. The purpose of this study was to determine the characteristics and nutritional status of children vaccinated against COVID-19 at UPT Puskesmas Kayon, Palangka Raya City. This type of research is a descriptive method, with a cross-sectional design, using a purposive sampling technique, for 3 months from July to September 2022. The research instruments used were a questionnaire and examination of nutritional status. The results showed that the number of respondents was 40 people, 52.5% female and 47.5% male. Age distribution from 6-11 years. Vaccination history at dose 1 20% and dose 2 80%. The nutritional status of the dominant respondents had a normal nutritional status of 67.5%, 20% less nutrition and 12.5% more nutritional status. The conclusion of this study shows that the age distribution of the most respondents is 11 years with the dominant nutritional status of respondents with normal nutritional status.